Pengembangan Buku Teks dalam Implementasi Kurikulum Merdeka di Sekolah Dasar - Tri Astari (Program Studi PGSD Universitas Madako Tolitoli, 2022)
The purpose of this research is to identify and obtain information about textbooks in the implementation of the Merdeka Curriculum in elementary schools. In addition, to see the availability of books for teachers and students. The method used in this research is descriptive qualitative. Research data collection techniques are documentation analysis, observation, and questionnaires (questionnaires). The findings in this study are that the distribution of Learning Outcomes in Merdeka Curriculum textbooks in Elementary Schools is not appropriate. This study concludes that the Merdeka Curriculum textbooks are available and consist of teacher manuals and student books on Religion subjects; Indonesian; Mathematics; Natural and Social Sciences; and English. But Pancasila Education; Sports Physical Education and health; and Arts and Culture (Music, Fine Arts, Theater Arts, and Dance Arts) only have teacher manuals. It is one of the problems in the implementation of the Merdeka Curriculum. The solution is for teachers to collaborate with fellow subject teachers in the same subject to make student books in a learning community or Teacher Working Group.